Evaluation of substance addiction through projective tests within the scope of skin-ego theory - Çinka, Elif; Tunaboylu İkiz, Emine Tevfika (Journal of Dependence, 2020)
Objective: This study was carried out to examine the features of the skin ego and functions of the excitation shield of patiens who are addicted to intrevenous heroin and synthetic cannabinoid with projective methods.Method: Thirty patients, 15 intravenous heroin users, 15 addicted to synthetic cannabinoid participated whose ages were between 18 and 45. The intravenous heroin users and synthetic cannabinoid users participated in a psychoanalytical oriented clinical interviews, Rorschach Test and Thematic Apperception Test. The content analysis of the data was based on the Paris School system and quantitative analysis was carried out.Result: The skin ego restructuring of the participants in both groups did not have sufficient stimulation barrier function and the shields of the stimulants were weak. In terms of self and identity designs, people who use intravenous heroin do not attribute aggressive or libidinal value to their designs and try to stay objective; and those who use synthetic cannabinoids can protect their body against internal and external stimuli.It was found that his integrity was felt under threat and his physical concerns were severe.Conclusion: Synthetic cannabinoid users were more fragile to the stimulation from inside and outside of their body and have lower barrier compared to the intravenous heroin users. Synthetic cannabinoid users have inadequate protection shields against excitation when faced with impulsive and affective experiences.
Keywords: Substance addiction; skin-ego; Rorschach test; Thematic Apperception Test